Ornithological Observations in Cocos Island and its Oceanic Waters, Costa Rica (July and September 2020) (Biocenosis, 2023)
The birdlife of Cocos Island  is complex in its distribution and presence. Ecotourism expeditions for birdwatching purposes contribute to understanding and expanding the knowledge, behavior, natural history, and presence of birds in remote locations. This work documents observations of behaviors and ornithological records that increase the presence of birds in the protected area and its oceanic waters. Four new records of species not previously documented on Cocos Island and one subspecies are included, common oceanic birds are suggested for the vast marine territory, and knowledge of the island’s resident and endemic birds is expanded. The two given expeditions correspond to July and September 2020, using the intensive search protocol on public access trails, and the eBird pelagic protocol on pelagic routes and circumnavigation of the island for the registration and documentation of bird species.
Keywords: oceanic birds; new records; birdwatching; endemic bird fauna; ecotourism